A pilot randomised controlled trial of abrupt versus gradual smoking cessation in combination with vaporised nicotine products for people receiving alcohol and other drug treatment. (August 2022) - Skelton, Eliza; Lum, Alistair; Robinson, Maryanne; Dunlop, Adrian; Guillaumier, Ashleigh; Baker, Amanda; Gartner, Coral; Borland, Ron; Clapham, Matthew; Bonevski, Billie
Highlights: VNPs in combination with a quit strategy were deemed acceptable by people accessing AOD treatment. A small proportion of participants quit smoking or significantly reduced the number of cigarettes per day. It is uncertain whether preference of quit strategy influenced cessation and cessation related behaviours, this will need to be examined in future studies. Abstract: Background: Vaporised nicotine products (VNPs) may be a potential quit smoking strategy. Most research has permitted participants to use VNPs ad libitum. This is the first study to examine combining the use of a VNP with a gradual or abrupt cessation guideline. This study aims to test the potential feasibility of a quit smoking strategy (abrupt verses gradual cessation) in combination with vaporised nicotine products among people in AOD treatment. Methods: We conducted a pilot randomised controlled trial between April 2018 and July 2019. Participants were recruited from AOD programs located within one area health service in Australia. Participants were provided with two VNPs, a 12-week supply of nicotine e-liquid and randomised to either the abrupt (assigned a quit date the day they were provided their VNP) or gradual quit smoking strategy (reduce baseline number of cigarettes per day by 25% over a 4 week period), no further behavioral support was provided. Feasibility was assessed through successful recruitment rates, retention, and adherence to study conditions. Participant perceived helpfulness and satisfaction assessed acceptability. Results: Among 80 interested individuals, 66 were eligible and consented (100% recruitment rate). From the 66 participants that consented and completed the baseline survey, 60 received the intervention assigned at a 1:1 ratio with 30 in the gradual cessation and 30 in the abrupt cessation group. Retention was 86.4% (n = 52) at 12-weeks post-intervention commencement. Ninety-six percent (n = 25) of participants in the gradual and 95.8% (n = 23) of participants in the abrupt group were using the VNPs at 12-weeks (p = 0.66). There was no difference in adherence to the assigned quit plan between gradual cessation 44% (n = 11) and abrupt cessation 71% (n = 17) groups (p = 0.117). Median perceived helpfulness of VNPs was high for both gradual (10/10) and abrupt (9/10) groups (p = 0.813). Similarly, median perceived satisfaction of VNPs was high for both gradual (9 /10) and abrupt (8/10) groups (p = 0.414). Conclusions: AOD participants found an intervention that involved VNPs to be satisfying and helpful. Future large scale trials are needed to elucidate whether a gradual or abrupt cessation guideline is more beneficial in main a quit attempt with a VNP.